Global financial crisis and southeast Asian trade performance: Empirical evidence - Kabir, S.; Bloch, Harry; Salim, Ruhul (2018)
© 2018 The Applied Regional Science Conference (ARSC) and John Wiley & Sons Australia, Ltd. The literature on the recent Global Financial Crisis (GFC) focuses on the decimation of Western economies; however, the impact of the crisis on Asian economies has remained largely unexplored. Using the classic dependency approach of the "core-periphery" framework, this paper investigates the trade performance of Association of South East Asian Nation (ASEAN) members during (2008-2009) and after (2010-2012) the GFC and analyses the transmission of shocks to these countries from the Western core. A modified gravity model of trade flows is estimated for a panel of five leading ASEAN economies and their trading partners for the period 2002-2012. The empirical results show a decline in ASEAN trade during the financial crisis that becomes stronger during the post-crisis period. The decline in trade exceeds that associated with changing gross domestic product at home and abroad, suggesting the crisis and its aftermath have been particularly disadvantageous for ASEAN trade.